PENGELOLAAN DANA OTONOMI KHUSUS BIDANG PENDIDIKAN DI KABUPATEN NABIRE - Makaria Tatogo; Theo Allo Layuk; Bonifasia Elitha Bharanti (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2018)
The objective of the research is to explore in depth the management process, and utilisation of Special Autonomy Fund provided for Education Sector for Native People in Nabire Regency. Methods of data collection using Observation, Interview, and Library Studies. We analyse the data utilising the qualitative approach. The results of this study reason some problems that are: unproperly managed, low synchronisation in planning, lack of coordination in implementation, and delay in reporting. Another problem is the socialisation of the funding regulation. Keywords: Special Autonomy, Management of OTSUS, Education, Triangulation